Electrochemistry of novel tetra peripherally and non-peripherally substituted phthalocyanines bearing morpholine groups - KOCA, ATIF (ELSEVIER SCIENCE SA, 2020)
Morpholine bearing phthalonitriles (3a and 3b) and peripherally and non-peripherally tetra substituted TiOPc and CuPc complexes (4a-5b) were prepared. Electrochemical responses of metallophthalocyanines were analysed and compared with each other in order to determine the influence of Cu2+ and TiO2+ metal centers and peripherally or non-peripherally substituents of the complexes. While CuPcs illustrated common Pc based reduction processes, TiOPcs showed extraordinary reduction peaks. During the oxidation processes, all complexes were electropolymerizable and metal centers and nonperipherally or peripherally substituents considerably affect electropolymerization processes. However, it was clearly seen that changing the positions of the substituents did not extensively influence the reduction processes. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Morpholine; Metallo-phthalocyanines; Electrochemistry; Electropolymerization; SPECTROELECTROCHEMICAL PROPERTIES; METAL-FREE; TITANYL PHTHALOCYANINES; THIN-FILMS; COPPER; COBALT(II); METALLOPHTHALOCYANINES; ELECTROPOLYMERIZATION; AGGREGATION; DERIVATIVES